The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000471932
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Ameliorates Diabetes-Associated Cognitive Decline by Regulating the Mitochondria-Mediated Apoptotic Pathway and IL-23/IL-17 Expression in db/db Mice

Abstract: Background: Diabetes-associated cognitive decline (DACD) is one of the complications of diabetes and leads to cognitive impairment and an increased risk of dementia. However, the exact mechanism of DACD has not been fully characterized, and a successful therapy for this issue has not been established. This study aimed to detect the anti-apoptotic and anti-inflammatory effects of hydrogen sulfide (H2S) on DACD. Methods: We used a behavioural scoring method, Western blot, TUNEL staining and immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
6
23
1
Order By: Relevance
“…This suggests that the effects of H 2 S on T cells are direct, rather than indirect through other immune cells present in the isolates, such as macrophages/microglia. The inhibitory effects of H 2 S on IL-17 generation in the CNS have been previously reported [63], thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the effects of H 2 S on T cells are direct, rather than indirect through other immune cells present in the isolates, such as macrophages/microglia. The inhibitory effects of H 2 S on IL-17 generation in the CNS have been previously reported [63], thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Various studies have confirmed that H 2 S attenuates ischemic brain injury by mitigating oxidative stress, inhibiting cell apoptosis, opening K-ATP channels, relaxing blood vessels, and alleviating astrocytic activation [13,14,29]. Consistent with these previous findings, we found that H 2 S improved neurological function and increased survival rate after CA and resuscitation in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…determined that endogenous H 2 S may be a special kind of neuromodulator. In the central nervous system (CNS), endogenous H 2 S is mainly generated through catalytic effects of 3-mercaptopyruvate sulfurtransferase and cystathionine-β-synthase on sulfur amino acids [13]. It is known that H 2 S is not only involved in the neuroendocrine adjustment by the hypothalamus-pituitary-adrenal axis [27], but also affects cerebral blood flow by relaxing microvascular smooth muscles [28].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 was also upregulated in all three diabetic models and was highly correlated with peripheral Aβ1-42 and with glucose levels in db/db mice. IL-17 is the most effective cytokine of T helper 17 cells and plays a proinflammatory role in chronic inflammation [73] observed in T2D [74]. Also, IL-17 production has been associated with cerebral small vessel disease, similar to that observed in db/db and APP/PS1xdb/db mice [75], and IL-17 might contribute to atherosclerosis development.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, IL-17 has been implicated in the neuroinflammatory response in AD [76], and while some controversial studies show a protective role for IL-17 against the risk for T2D [77], others support a crucial role for IL-17 in inflammation, insulin resistance, and T2D [66,78]. In line with these studies, IL-17 levels are also increased in the hippocampus from db/db mice [73], and antibodies targeting Th17 cells have been studied in an effort, to protect individuals at risk for developing diabetes [79]. These data support that metabolic alterations can broadly trigger and exacerbate brain neuroinflammation and production of cytokines known to promote T2D and AD pathogenesis [36,79].…”
Section: Discussionmentioning
confidence: 75%